Implementation of Enterprise Resource Planning Inventory and Point of Sales Module (Study Case at XYZ Distributor Company) - Adellyna Cantica Febbyanti; Renny Sari Dewi (Journal of Digital Business and Innovation Management, 2025)
This study aims to implementation of an Enterprise Resource Planning (ERP) system using Inventory and Point of Sales (POS) modules in the XYZ distributor company. ERP was chosen as a solution to address the challenges faced by the company in managing stock and sales transactions, which were still performed manually, often leading to data inaccuracies and operational inefficiencies. The Quickstart Odoo method was employed for system development due to its effective, efficient, and structured approach. The research involved analyzing existing business processes, identifying gaps, and configuring the ERP system to align with the company's needs. Data collection was conducted through stakeholder interviews and literature reviews. The implementation of the Inventory module provided real-time visibility into stock levels, enhancing inventory management efficiency, while the POS module automated sales transactions and enabled real-time data consolidation.